2014
DOI: 10.4049/jimmunol.1400348
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific Naive CD8+ T Cells Produce a Single Pulse of IFN-γ In Vivo within Hours of Infection, but without Antiviral Effect

Abstract: In vitro studies have shown that naïve CD8+ T cells are unable to express most of their effector proteins until after at least one round of cell division has taken place. We have re-assessed this issue in vivo, and find that naïve CD8+ T cells mount antigen-specific responses within hours of infection, before proliferation has commenced. Newly-activated naïve antigen specific CD8+ T cells produce a rapid pulse of IFNγ in vivo and begin to accumulate granzyme B and perforin. Later, in vivo cytolytic activity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 66 publications
1
34
0
Order By: Relevance
“…It is also noteworthy that a TCR signal is sufficient for MAIT cells to elicit a brief TNF-α and IFN-γ pulse 6 hours after TCR stimulation. This is akin to what has been described in naive CD8 + T cells, which also briefly make IFN-γ early after activation and prior to their first cell division (39). We could not detect significant production of IFN-γ in MAIT cells by intracellular cytokine staining at later time points (Figure 1B) or in MAIT cell culture supernatant by Luminex analysis (Figure 2A) 24 hours after stimulation, further arguing that the production is very brief and limited.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It is also noteworthy that a TCR signal is sufficient for MAIT cells to elicit a brief TNF-α and IFN-γ pulse 6 hours after TCR stimulation. This is akin to what has been described in naive CD8 + T cells, which also briefly make IFN-γ early after activation and prior to their first cell division (39). We could not detect significant production of IFN-γ in MAIT cells by intracellular cytokine staining at later time points (Figure 1B) or in MAIT cell culture supernatant by Luminex analysis (Figure 2A) 24 hours after stimulation, further arguing that the production is very brief and limited.…”
Section: Discussionsupporting
confidence: 59%
“…We could not detect significant production of IFN-γ in MAIT cells by intracellular cytokine staining at later time points (Figure 1B) or in MAIT cell culture supernatant by Luminex analysis (Figure 2A) 24 hours after stimulation, further arguing that the production is very brief and limited. A previous study demonstrated that this brief IFN-γ pulse does not result in antiviral immunity, and thus, the purpose is still unclear (39). An IFN-γ response following TCR stimulation was reported in MAIT cell clones and lines (28, 40), which are useful tools to identify antigens but not a suitable substitute for studying ex vivo activation requirements of primary human T cells.…”
Section: Discussionmentioning
confidence: 99%
“…This rapid viral control, which occurred in the absence of concurrent IFNγ synthesis by CD8 + memory T cells, suggests that the pulse of IFNγ is not directly antiviral and, instead, may be immunoregulatory. This led us also to consider the possibility that IFNγ, itself, might mediate the active, TCR-independent suppression of CD8 + memory T cell responses, because it is abundantly produced by antigen-specific CD8 + T cells immediately following primary viral infection (Hosking et al , 2014), secondary viral infection (Hosking et al , 2013), and peptide stimulation (this study), and a pulse of IFNγ synthesis invariably preceded the onset of the suppressed state. To test this hypothesis, we administered recombinant IFNγ directly to LCMV-immune mice, then infected the mice with LCMV and assessed in vivo IFNγ production by LCMV-specific CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…As previously detailed (Foster et al , 2007; Hosking et al , 2013; Hosking et al , 2014; Liu and Whitton, 2005; Whitmire et al , 2008b), 250 µg of Brefeldin A (Sigma St Louis, MO) was injected i.v. into peptide and/or virus challenged LCMV immune mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation